The real exchange rate, innovation and productivity - Laura Alfaro; Alejandro Cunat; Harald Fadinger; Yanping Liu (University of Mannheim, Department of Economics, 2017)
We evaluate manufacturing firms' responses to changes in the real exchange rate (RER) using detailed firm-level data for a large set of countries for the period 2001-2010. We uncover the following stylized facts: In emerging Asia, real depreciations are associated with faster growth of firm-level TFP, sales and cashow, higher probabilities to engage in R&D and export. We find no significant effects for firms from industrialized economies and negative effects for firms in other emerging economies, which are less export-intensive and more import-intensive. Motivated by these facts, we build a dynamic model in which real depreciations raise the cost of importing intermediates, but increase demand and the profitability to engage in exports and R&D, thereby relaxing borrowing constraints and enabling more firms to overcome the fixed-cost hurdle for financing R&D. We decompose the effects of RER changes on productivity growth into these channels and explain regional heterogeneity in the effects of RER changes in terms of differences in export intensity, import intensity and financial constraints. We estimate the model and quantitatively evaluate the different mechanisms by providing counterfactual simulations of temporary real exchange rate movements. Effects on physical TFP growth, while different across regions, are non-linear and asymmetric.
urn:nbn:de:bsz:180-madoc-431634
Keywords: F0; O0; 330; real exchange rate; firm level data; innovation; productivity; exporting; importing; credit constraints